Dose‐response effects of light at night on the reproductive physiology of great tits (Parus major): Integrating morphological analyses with candidate gene expression. Issue 8 (29th July 2018) - Dominoni, Davide M.; de Jong, Maaike; Bellingham, Michelle; O'Shaughnessy, Peter; van Oers, Kees; Robinson, Jane; Smith, Bethany; Visser, Marcel E.; Helm, Barbara
Abstract: Artificial light at night (ALAN) is increasingly recognized as a potential threat to wildlife and ecosystem health. Among the ecological effects of ALAN, changes in reproductive timing are frequently reported, but the mechanisms underlying this relationship are still poorly understood. Here, we experimentally investigated these mechanisms by assessing dose‐dependent photoperiodic responses to ALAN in the great tit ( Parus major ). We individually exposed photosensitive male birds to one of three nocturnal light levels (0.5, 1.5, and 5 lux), or to a dark control. Subsequent histological and molecular analyses on their testes indicated a dose‐dependent reproductive response to ALAN. Specifically, different stages of gonadal growth were activated after exposure to different levels of light at night. mRNA transcript levels of genes linked to the development of germ cells ( stra8 and spo11 ) were increased under 0.5 lux compared to the dark control. The 0.5 and 1.5 lux groups showed slight increases in testis size and transcript levels associated with steroid synthesis ( lhr and hsd3b1 ) and spermatogenesis ( fshr, wt1, sox9, and cldn11 ), although spermatogenesis was not detected in histological analysis. In contrast, all birds under 5 lux had 10 to 30 times larger testes than birds in all other groups, with a parallel strong increase in mRNA transcript levels and clear signs of spermatogenesis. Across treatments, the volume of the testes was generally a good predictor of testicular transcript levels. Overall, our findings indicate that even small changes in nocturnal light intensity can increase, or decrease, effects on the reproductive physiology of wild organisms. GRAPHICAL ABSTRACT: – First experimental study assessing dose‐dependent responses of avian reproductive physiology to artificial light at night – Different stages of gonadal growth were activated after exposure to different levels of light at night – Body size and spermatogenesis were affected only at the highest level used, 5 lux – Artificial light at night advances reproductive growth in a dose‐dependent manner